Implementasi Self-Direct Learning untuk Meningkatkan Keterampilan Siswa dan Staff Pengajar Pasca Covid - Ummiati Rahmah; Mahmud Mustapa; Nur Azizah Eka Budiarti (Universitas Negeri Makassar, 2023)
Since the COVID-19 pandemic, many learning methods have been developed so that the teaching and learning process continues, including Self-Directed Learning. Self-Directed Learning is a learning model used by teaching staff to develop student skills because it emphasizes responsibility for managing learning objectives independently. Self-directed learning gives learners the freedom and autonomy to decide what, why, how and where they want to learn. The pupose od this study is to see the quality of the Self-Directed Learning learning model reviewed through a literature review.A Literature review are the process of collecting relevant articles from 2010-present. From the tens of articles obtained, we have selection and data extraction that fit the purposes of this reseaech. In the finalization of the article are based on the object and the approach.Based on the findigs of this research project, elf-Directed Learning is widely used to assess students' level of competence and initiative in learning and to enhance teachers' creativity in presenting learning materials. The results of this study suggest that the learning method can improve student learning outcomes, as be proven by results above the average pass threshold, and is highly adaptable to improve student competence on independent learning.The contribution of this study is to provide guidance to educators and researchers on self-directed learning methods of learning that are appropriately applied to enhance student learning, especially in the wake of the COVID-19 pandemic. Also, when learning, there is also a view that focusing only on the learning object can be directed to the learning subject.